Implementasi Kebijakan Suroboyo Bus Sebagai Transportasi Publik - Alifianka Prila Permata; Tukiman Tukiman (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
The Suroboyo Bus policy was introduced as public transportation in Surabaya City. This research aims to understand and analyze the Implementation of Suroboyo Bus Policy as Public Transportation in Surabaya City. This research will describe how the implementation of the Suroboyo Bus Policy as Public Transportation in Surabaya City uses the theory of G. Shabbir Cheema and Dennis A. Rondinelli with a qualitative research method with a descriptive approach. The results showed that the implementation of Suroboyo Bus as Public Transportation in Surabaya City was not as planned. This is due to the limited budgeting provided by the Surabaya City Government, resulting in the inability to provide maximum service to Suroboyo Bus users.